Pre-validation of a Calu-3 epithelium cytotoxicity assay for predicting acute inhalation toxicity of chemicals. (September 2021) - Jeong, Mi Ho; Han, Yubin; Oh, In-Sun; Kim, Dong Min; Son, Dong-Won; Jung, Mi-Sook; Yang, Hyoseon; Lee, Kyuhong; Shin, Ju-Young; Kim, Ha Ryong; Chung, Kyu Hyuck
Abstract: Although in vivo inhalation toxicity tests have been widely conducted, the testing of many chemicals is limited for economic and ethical reasons. Therefore, we previously developed an in vitro acute inhalation toxicity test method. The goal of the present pre-validation study was to evaluate the transferability, reproducibility, and predictive capacity of this method. After confirming the transferability of the Calu-3 epithelium cytotoxicity assay, reproducibility was evaluated using 20 test substances at three independent institutions. Cytotoxicity data were analyzed using statistical methods, including the intra-class correlation coefficient and Bland-Altman plots for within- and between-laboratory reproducibility. The assay for the 20 test substances showed excellent agreement within and between laboratories. To evaluate the predictive capacity, 77 test substances were analyzed for acute inhalation toxicity. Accuracy was measured using a cutoff of 40%, and the relevance was analyzed as a receiver-operating characteristic (ROC) curve. An accuracy of 72.73% was obtained, and the area under the ROC curve was 0.77, indicating moderate performance. In this study, we found that the in vitro acute inhalation toxicity test method demonstrated good reliability and relevance for predicting the acute toxicity of inhalable chemicals. Hence, this assay has potential as an alternative test for screening acutely toxic inhalants. Highlights: Our study pre-validated a Calu-3 epithelium cytotoxicity assay for determining acute inhalation toxicity evaluiating transferability, reproducibility, and predictive capacity test. Statistical analyses such as intra-class correlation and Bland-Altman plot demonstrated the excellent reproducibility of the Calu-3 epithelium cytotoxicity assay. The performance, i.e., accuracy, of the Calu-3 epithelium cytotoxicity assay, was moderate (72.73%) using 77 test substances. As a consequence of its excellent transferability, reproducibility, and moderate accuracy, the Calu-3 epithelium cytotoxicity assay might be broadly used for screening acutely toxic inhalants.